Analisis Pengaruh Pemerataan Pembangunan Infrastruktur terhadap Pertumbuhan Ekonomi di Sumatera Utara - Awaliyah Matondang, Khairani; Rahel Hutahaean; Veranita Sitio; Manurung, Eka Valentina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the influence of equitable infrastructure development on economic growth in North Sumatra using a literature review approach. With a focus on the regional context of North Sumatra, this research explores the link between infrastructure development and economic development in the region. The literature review method is used to develop a conceptual framework, analyze empirical findings, and identify key factors that influence the relationship between infrastructure and economic growth. Through a comprehensive literature synthesis, this research is expected to provide in-depth insight into the impact of equitable infrastructure development on regional economic growth in North Sumatra, providing a basis for more effective and sustainable policies in encouraging regional development.